2004
DOI: 10.1073/pnas.0307880101
|View full text |Cite
|
Sign up to set email alerts
|

Matefin, a Caenorhabditis elegans germ line-specific SUN-domain nuclear membrane protein, is essential for early embryonic and germ cell development

Abstract: Caenorhabditis elegans mtf-1 encodes matefin, which has a predicted SUN domain, a coiled-coil region, an anti-erbB-2 IgG domain, and two hydrophobic regions. We show that matefin is a nuclear membrane protein that colocalizes in vivo with Ce-lamin, the single nuclear lamin protein in C. elegans, and binds Ce-lamin in vitro but does not require Ce-lamin for its localization. Matefin is detected in all embryonic cells until midembryogenesis and thereafter only in germ-line cells. Embryonic matefin is maternally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
106
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 30 publications
2
106
0
Order By: Relevance
“…Anc-1, in turn, interacts with the actin cytoskeleton to anchor the nucleus. A similar model has been elaborated for the role of a second C. elegans SUN domain protein, Sun1/Matefin, in mediating interaction of the nucleus with the centrosome (29,33), and the mammalian Sun1 and Sun2 proteins also are implicated in bridging the nuclear envelope (54,55). A role for the actin cytoskeleton in bouquet formation is suggested by the cessation of telomere clustering during meiotic prophase in S. cerevisiae after addition of latrunculin, which depolymerizes actin filaments (14).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Anc-1, in turn, interacts with the actin cytoskeleton to anchor the nucleus. A similar model has been elaborated for the role of a second C. elegans SUN domain protein, Sun1/Matefin, in mediating interaction of the nucleus with the centrosome (29,33), and the mammalian Sun1 and Sun2 proteins also are implicated in bridging the nuclear envelope (54,55). A role for the actin cytoskeleton in bouquet formation is suggested by the cessation of telomere clustering during meiotic prophase in S. cerevisiae after addition of latrunculin, which depolymerizes actin filaments (14).…”
Section: Discussionmentioning
confidence: 89%
“…SUN domain proteins are present in eukaryotes from fungi to vertebrates, and SUN domains are proposed to be protein interaction domains (28,29,31,32,35,51,52). Unc-84, an inner nuclear membrane protein, is proposed to bridge the perinuclear space to interact with a second protein, Anc-1, of the outer nuclear envelope (32,37,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in flies, the SUN protein Klaroid is required for the localization of KASH protein Klarsicht to the NE and for nuclear migration in the eye (15). Genetic studies in the worm and yeast also have indicated roles of SUN proteins in mediating the interactions between the NE and centrosome, centromeres, and telomeres at various stages of mitotic and meiotic cells (16)(17)(18)(19)(20)(21)(22).Mammalian SUN1 and SUN2 proteins were first identified as homologues of C. elegans UNC-84 (10). SUN1 and SUN2 are broadly distributed in mouse tissues, whereas 2 other, more recently identified SUN proteins, SUN3 and SPAG4, appear to be expressed in a limited amount of tissues (4,(23)(24)(25).…”
mentioning
confidence: 99%
“…Similarly, in flies, the SUN protein Klaroid is required for the localization of KASH protein Klarsicht to the NE and for nuclear migration in the eye (15). Genetic studies in the worm and yeast also have indicated roles of SUN proteins in mediating the interactions between the NE and centrosome, centromeres, and telomeres at various stages of mitotic and meiotic cells (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%